Bilingual Intercultural Education in Contexts of Linguistic Displacement: The Upshijgra din̈ Diⱽ Tegát yet Project (Costa Rica) - Guevara-Víquez, Federico (2024)
The article presents the experience developed within the Upshijgra din̈ Di ⱽ Tegát yet project, led by the Permanent Support Program for Indigenous Schools (PAPEI) of the Division of Rural Education (DER) at the National University of Costa Rica. Its primary objective is to strengthen bilingual intercultural education in the Boruca territory for teaching the Brunca language, with participation from language teachers in circuit 11 of the Grande de Térraba Regional Educational Directorate. The methodology follows a qualitative orientation of participatory action research, using language teaching techniques based on the communicative approach. The main finding underscores the importance of enhancing linguistic competencies among teachers of Language and Culture and supporting the development of mediation strategies and didactic materials to bolster school processes for these subjects at the primary level. The primary conclusion reveals growth in teachers' communicative skills in the indigenous language and in creating didactic materials for these subjects.